Wenckebach cycle length: A novel predictor for AV block in AVNRT patients treated with ablation. Issue 9 (28th August 2021) - Chatzidou, Sofia; Kontogiannis, Christos; Georgiopoulos, Georgios; Kosmopoulos, Marinos; Pateras, Konstantinos; Spartalis, Michael; Stamatelopoulos, Kimon; Rokas, Stelios
Abstract: Background: Radiofrequency catheter ablation remains the most effective management option for atrioventricular nodal reentry tachycardia (AVNRT). The risk of atrioventricular (AV) block requiring permanent pacemaker is substantial, but, currently, a reliable method to predict this complication is lacking. Methods: The electrophysiologic studies (EPS) and baseline characteristics of patients who underwent catheter ablation for the treatment of AVNRT were retrospectively analyzed to investigate predisposing factors for AV block after treatment. Patients were followed for AV block at one month and one year after hospital discharge. Results: Among 784 patients treated with catheter ablation for AVNRT between 1999 to 2019, 15 developed AV block. Patients with AV block were older ( p  = .001). Among the recorded EPS parameters, patients with AV block had significantly higher Atrial His interval (120 vs. 110 ms, p  = .049), Wenckebach cycle length (WCL) (400 vs. 353 ms, p  < .001) and tachycardia CL (400 vs. 387 ms, P  = .01) during the ablation compared to their peers without AV block. Additionally, only WCL (OR = 1.1, 95% CI 1.02‐1.19, p  = .017) remained significant after adjustment for age, gender, ERP, AH interval, and HR. This association was confirmed by comparing patients with (n = 15) and without (n = 15) AV block using propensity score‐matching. A WCL≥400ms was associated with a 4‐fold higher incidence of AV block (4.79% vs. 1.25%). Conclusion: Increased pre‐procedural WCL was associated with a high risk for AV block after catheter ablation treatment for AVNRT. These findings suggest that this readily available EPS‐derived parameter may be a novel marker of risk for severe complications in these patients.